Microsoft Access version 2002 : step by step. - Online Training Solutions (Redmond : Microsoft, 2001)
Samenvatting:Microsoft Access Version 2002 provides powerful new tools with which tomanage data, share information with coworkers over an intranet or theInternet, find and retrieve answers faster, leverage automated,pre-packaged databases to quickly build business solutions, and integratethose solutions with Microsoft SQL Server(tm) 2000. MICROSOFT ACCESSVERSION 2002 STEP BY STEP offers self-paced instruction to thebeginning-to-advanced user who wants to get the most out of Access-andprepare for Microsoft Office User (MOUS) certification. This personaltraining system offers easy-to-follow lessons full of clear objectives, awealth of task-oriented procedures, and dozens of real-world businessscenarios. Each STEP BY STEP title consists of friendly, straightforwardinstruction with dozens of full-color screenshots and illustrations tohelp you learn exactly what you need to know at your own pace. Acompanion CD-ROM includes practice files that are tightly integrated withthe lessons, plus movie-style demonstrations of key procedures. Otherfeatures include a "QuickLook Guide" for easy visual navigation, a"Finding the Best Starting Point for You" section to help you decide howto the most out of the book, and a special lay-flat binding to keep thebook open during lessons.
CD-rom included
Keywords: Access; Computerprogramma's.